Early detection of bacterial diseases in apple plants by analysis of volatile organic compounds profiles and use of electronic nose. (16th February 2016) - Cellini, A.; Biondi, E.; Blasioli, S.; Rocchi, L.; Farneti, B.; Braschi, I.; Savioli, S.; Rodriguez‐Estrada, M.T.; Biasioli, F.; Spinelli, F.
Abstract : DNA‐based protocols are the standard methods for the diagnosis of infected plant material. Nevertheless, these methods are time‐consuming and require trained personnel, with an efficacy depending on the sampling procedure. In comparison, recognition methods based on volatile compounds emissions are less precise, but allow a non‐destructive mass screening of bulk samples, and may be implemented to steer molecular diagnosis. In this study, the analysis of volatile compounds is used for the discrimination of fire blight ( Erwinia amylovora ) and blossom blight ( Pseudomonas syringae pv. syringae ) on apple propagation material. Possible marker compounds were identified by gas chromatography–mass spectroscopy (GC‐MS) and proton transfer reaction‐time of flight‐mass spectroscopy (PTR‐ToF‐MS). In addition, two commercial electronic noses were used for diagnosis. After a preliminary validation in vitro, a diagnostic protocol was successfully developed to scale up to real nursery conditions on cold stored, asymptomatic dormant plants.